Mediation as an alternative dispute resolution in family disputes / Sa’odah Ahmad, Rojanah Kahar and Muslihah Hasbullah - Ahmad, Sa’odah; Kahar, Rojanah; Hasbullah, Muslihah (Faculty of Administrative Science and Policy Studies, 2012)
The traditional approach in resolving family dispute is adversarial in nature where the parties argue over matters pertaining to ownership of property, future financial management and custody of children. According to this approach, dispute is likened to a battle where one party will be the winner and the other party will be the loser. This litigation process is normally time consuming, parties in dispute feel less satisfied with the decision and also involves higher legal fees. Sometimes, the court’s decision does not fully take into account the welfare and interest of the children and the psychological aspect of parties involve in the dispute. The current trend in the family laws of several countries like Singapore, Australia and United States of America is to give priority to the alternative method in resolving family disputes. This trend is resulted from general dissatisfaction with the procedural aspects of the law and the ineffectiveness of the provisions intended to encourage reconciliation that can benefit all parties involved in the dispute. This alternative method is known as mediation or sulh in Islamic law. Family mediation tries to help the disputants in handling impacts resulted from family disputes. In Malaysia, the application of a courtbased sulh, as an alternative method in resolving family disputes among the Muslims is still limited. Empirical studies conducted in the Selangor Judicial Department and the Syariah Court of Federal Territories revealed that in general, the approach of resolving dispute amicably through sulh provide satisfaction among the parties in disputes with regard to the resolution or agreement achieved. Besides, with the help of the sulh officer as a mediator, the disputants were able to discuss their problem rationally and try to find the best solution themselves. This amicable resolution preserves well being and healthy relationship not only among the disputants but also the children of the marriage. It can be also concluded that sulh is in line with one of the strategic thrusts of the National Family Policy i.e. to ensure that laws, policies, procedures and enforcement of laws prioritize the family well being perspective.